Changes in cognitive function after a 12-week exercise intervention in adults with Down syndrome. Issue 3 (July 2018) - Ptomey, Lauren T.; Szabo, Amanda N.; Willis, Erik A.; Gorczyca, Anna M.; Greene, J. Leon; Danon, Jessica C.; Donnelly, Joseph E.
Abstract: Background: Between 250, 000 and 400, 000 individuals in the United States are diagnosed with Down syndrome (DS). Nearly all adults with DS will develop Alzheimer's disease pathology starting in their thirties. Recent studies suggest that increased physical activity (PA) may be important for maintaining components of cognition, including memory. Objective: The purpose of this study was to evaluate changes in cognitive function after completion of a 12-week exercise intervention in adults with DS. Methods: Participants were randomized to attend 30-minute group exercise sessions 1 or 2 times a week for 12 weeks. The exercise sessions were delivered via video conferencing on a tablet computer to groups of 5–8 participants. Sessions consisted of aerobic based exercises such as walking and jogging to music, dancing, as well as strength based exercises such as vertical jumps, bicep curls, and squats. Cognitive function was measured at baseline and end of study using the Cantab Dementia Battery for iPads, which assessed the cognitive domains of memory, attention, and reaction time. Results: Twenty-seven participants (27.9 ± 7.1 years of age, 40.7% female) enrolled and completed the 12-week intervention. Participants randomized to 1 session/week averaged 26.6 ± 3.0 min/week of PA from the group exercise session. Participants randomized to 2 sessions/week averaged 57.7 ± 15.3 min/week of PA from the group exercise sessions. Participants improved their performance on the two memory variables (p = 0.048 and p = 0.069). Conclusion: Increased exercise may have positive changes on memory and other cognitive functions.